EMOTIONAL INTELIGENCE THE PRESCPECTIVE OF DANIEL GOLEMAN AND ITS RELEVANCE IN ISLAMIC EDUCATION - Ivan Riyadi (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2015)
This articel was conducted based on the consideration that the current emotional intelligence is still indispensable in shaping the behavior of students. With specifying on the subjects of Islamic education. This article tried to connect the emotional intelligence of high school students on Islamic Education. This article examines to determine how Islamic religious education policies that have been implemented in high school and to determine the relevance of emotional intelligence of high school students against the teachings of Islam. To get a complete this article. libarary research approach. Data was collected through literature study includes studying, studying and citing theories or concepts from a number of literature. Books, journals, magazines and others. It can be applied to educate children who are emotionally intelligent with the ability to recognize self-managing emotions productively utilize emotions, empathy, and the ability to build social relationships.